Potential Use of Biological Herbicides in a Circular Economy Context: A Sustainable Approach - Stefanski, Fábio Spitza; Camargo, Aline Frumi; Scapini, Thamarys; Bonatto, Charline; Venturin, Bruno; Weirich, Sabrina Natalia; Ulkovski, Cleiton; Carezia, Carine; Ulrich, Alessandro; Michelon, William; Soares, Hugo Moreira; Mathiensen, Alexandre; et al. (Frontiers in Sustainable Food Systems, 2020)
In recent years, synthetic herbicides' intense and disordered use has triggered severe contamination of soils and water bodies, causing damage to living organisms, including vegetal herbicide-resistance. In-part, biological herbicides, offer promise in addressing these problems, especially for sustainable weed management in both agricultural and natural resource management contexts. The search for culture media to serve as alternatives to the existing conventional synthetic media has focused on microalgae biomass. The natural properties of these organisms make them ideal raw materials for fermentative processes. Therefore, this study aimed to integrate bioprocesses producing bioherbicidal extract using a submerged fermentation process. For this, a substrate of microalgae recycled biomass to replace commercially used media for fungal growth for relatively cheap biomass obtained from wastewater phycoremediation after anaerobic treatment (UASB). We also verified its potential for weed control. Preliminary tests of microalgae fermentation were conducted in the raw and lyophilized form, using the fungus Trichoderma koningiopsis. To evaluate their phytotoxic potential, the biocompounds were applied to Bidens pilosa, Conyza bonariensis, Urochloa plantaginea, and Euphorbia heterophylla weeds. A central composite rotatable design (CCRD) was used to evaluate the influence of temperature (20–45°C), agitation (0–200 RPM), and pH (3–14) on the improvement of enzyme activities, fungal growth and the effects on Cucumis sativus germination tests. We found that microalgae could be used as a substrate for obtaining bioherbicides. The biocompounds produced in this study were relevant for pre- and post-emergence control of model plants (Cucumis sativus), with vigor indexes of up to 8.05% and herbicide-resistant plants (Conyza bonariensis) with phytotoxic damage of up to 100% after 15 days. From the experiments' design, we found that agitation was the variable that had the most significant effect on enzyme and biomass production, followed by pH and temperature. The enzymes also showed synergistic action when acting together with microalgae and fungi, potentiating the control effect on weeds. Finally, the system integrated bioprocesses through agro-industrial effluent recovery and reuse, considered one of the essential economic viability mechanisms by enhancing the development of more sustainable technologies that embrace the principles of a circular economy.